The Journey of Liu Xiaobo : From Dark Horse to Nobel Laureate - Liu, Xiaobo, 1955-2017; Worden, Andrea; Mosher, Stacy; Leedom-Ackerman, Joanne, 1948- (Book collections on Project MUSE., 2020)
"The Journey of Liu Xiaobo is a fitting tribute to Liu Xiaobo's memory and to his influence, which even after his death, continues to grow."--